SIMEX : Singapore International Monetary Exchange - Ler, Adrian (2015)
As partial fulfilment of the B.Bus Degree, it is compulsory for every fmal year students to complete a research project in their field of interest. Thus, the students have done an in-depth study on SIMEX and come up with this repmt which will gives a better understanding of how Singapore International Monetary Exchange (SIMEX) works and some of the issues it faces. This report is divided into eight chapters. It provides the readers a general background of SIMEX as well as the evolution of SIMEX i11 the first two chapters. The report also gives a in depth review of the operating system of SIMEX as well as a study on the major driving forces behind its growih and success. In addition, it explicits some of the challenges that SIMEX might face in the foreseeable future and how SIMEX has poised itself to take on such challenges. Furthermore, an analyzed results of the students' survey among the SIMEX's members were incorporated in this report to give the readers a more pragrnatic view of the issues actually faced by its members. Last but not least, this report provides a summruy on the vanous aspects discussed to give the readers a better overall understanding of SIMEX and a conclusion on whether or not SIMEX is poised to maintain its position as the leading fmancial futures exchange in the Asia Pacific region.